2004
DOI: 10.1016/j.cell.2004.09.001
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans LIN-18 Is a Ryk Ortholog and Functions in Parallel to LIN-17/Frizzled in Wnt Signaling

Abstract: Wnt proteins are intercellular signals that regulate various aspects of animal development. In Caenorhabditis elegans, mutations in lin-17, a Frizzled-class Wnt receptor, and in lin-18 affect cell fate patterning in the P7.p vulval lineage. We found that lin-18 encodes a member of the Ryk/Derailed family of tyrosine kinase-related receptors, recently found to function as Wnt receptors. Members of this family have nonactive kinase domains. The LIN-18 kinase domain is dispensable for LIN-18 function, while the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
174
2
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(185 citation statements)
references
References 57 publications
7
174
2
2
Order By: Relevance
“…1 F and G) (26), cog-1 and lin-11, in turn, control the expression pattern of egl-17 and cdh-3. Patterns of egl-17 and cdh-3 expression observed in lin-17 and lin-18 mutants are consistent with high levels of cog-1 and lin-11 turning on the expression of these genes (31,32). Another set of cell-fatepatterning mechanisms controlling gene expression was revealed by the analysis of vulE vs. vulF fate specification using the zmp-1 reporter.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…1 F and G) (26), cog-1 and lin-11, in turn, control the expression pattern of egl-17 and cdh-3. Patterns of egl-17 and cdh-3 expression observed in lin-17 and lin-18 mutants are consistent with high levels of cog-1 and lin-11 turning on the expression of these genes (31,32). Another set of cell-fatepatterning mechanisms controlling gene expression was revealed by the analysis of vulE vs. vulF fate specification using the zmp-1 reporter.…”
Section: Resultsmentioning
confidence: 73%
“…1 A). Although the full mechanism that establishes this pattern is not known, Wnt signals, mediated by lin-17 (Frizzled-type Wnt receptor) and lin-18 (Ryk-type Wnt receptor), control the anterior͞posterior order of cell types among P7.p descendants (31,32) (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been shown that the Wnt pathway is involved in the generation of the P. pacificus vulva (13,14,22). In a similar fashion, in C. elegans, Wnt signaling is also required at different times in development to generate both a functional gonad and a functional vulva (15,16,(23)(24)(25)(26). Although the exact roles in specific cell-fate decisions within these lineages are likely to be quite different between P. pacificus and C. elegans, it is tempting to speculate that alterations in the timing and spatial expression of Wnt ligands or Frizzled receptors in vulval and gonadal lineages, respectively, may be responsible for the change in organ shape that we describe here.…”
Section: Discussionmentioning
confidence: 92%
“…Two major classes of receptors mediate Wnt action, Frizzleds and Ryk/Derailed. Both classes of receptors are also involved in earlier functions, such as cell fate determination (Wodarz and Nusse, 1998;Halford et al, 2000;Inoue et al, 2004). There is no compelling evidence that Drosophila frizzled genes interact with derailed (Yoshikawa et al, 2003).…”
Section: Specificitymentioning
confidence: 99%